Concise principles of company law in Malaysia - Rachagan, Shanthy; Pascoe, Janine; Joshi, Anil (LexisNexis, 2010)
Chapter 1 Introductions to Malaysian Company Law -- Chapter 2 Incorporation and Its Effects -- Chapter 3 Types of Companies -- Chapter 4 The Company Constitution: Memorandum and Articles -- Chapter 5 The Company's Relations with Outsiders -- Chapter 6 Promoters and Pre-incorporation Contracts -- Chapter 7 Prospectuses -- Chapter 8 Share Capital -- Chapter 9 Membership -- Chapter 10 Dividends -- Chapter 11 Debentures and Loan Capital -- Chapter 12 Directors -- Chapter 13 Corporate Governance and Duties of Directors -- Chapter 14 Meetings -- Chapter 15 Company Accounts and Annual Returns -- Chapter 16 Auditors -- Chapter 17 Member's Remedies -- Chapter 18 Takeovers -- Chapter 19 Prohibited Market Practices -- Chapter 20 Inspections -- Chapter 21 Schemes of Arrangement -- Chapter 22 Receivership -- Chapter 23 Liquidations